PENILAIAN KINERJA KEPALA SEKOLAH DAN GURU MUHAMMADIYAH KECAMATAN TEMPEL - Dedy Setyawan; Muhammad Zuhaery (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The research objectives: (1) measure the performance appraisal of the principal (2) measure the teacher's performance appraisal (3) determine the relationship between the principal's performance appraisal and the teacher's performance appraisal. This research is a quantitative descriptive. Respondents in this study 9 principals and 41 teachers who have been certified. Data collection techniques used questionnaires and documentation. Based on the results of research with good categories, it is shown as follows: (1) personality and social competence 65% good category (2) leadership competence 62% good category (3) school development competence 64% good category (4) resource competence 61% good category (5) entrepreneurial competence 59% good category (6) learning supervision competence with 55% good category. The results of the principal's assessment are in the good category. Teacher performance assessment with the following results; (1) pedagogic competence 65% good category (2) personality competence 64% good category (3) social competence 69% good category (4) professional competence 60% good category